2011
DOI: 10.1016/j.chembiol.2011.10.018
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Discrimination Map of the Antibiotic Resistance Kinome

Abstract: Kinase-mediated resistance to antibiotics is a significant clinical challenge. These enzymes share a common protein fold characteristic of Ser/Thr/Tyr protein kinases. We screened 14 antibiotic resistance kinases against 80 chemically diverse protein kinase inhibitors to map resistance kinase chemical space. The screens identified molecules with both broad and narrow inhibition profiles, proving that protein kinase inhibitors offer privileged chemical matter with the potential to block antibiotic resistance. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 56 publications
4
74
0
Order By: Relevance
“…353 The notion of directly inhibiting resistance elements, thereby rescuing antibiotic activity, is not confi ned to the β-lactam antibiotics. Eff orts to block aminoglycoside-inactivating enzymes 354 and antibiotic effl ux pumps 355 have also proven eff ective in vitro, though none have progressed to clinical trials yet.…”
Section: Adjuvantsmentioning
confidence: 99%
“…353 The notion of directly inhibiting resistance elements, thereby rescuing antibiotic activity, is not confi ned to the β-lactam antibiotics. Eff orts to block aminoglycoside-inactivating enzymes 354 and antibiotic effl ux pumps 355 have also proven eff ective in vitro, though none have progressed to clinical trials yet.…”
Section: Adjuvantsmentioning
confidence: 99%
“…Efforts to overexpress Rgt1438 in E. coli failed despite numerous attempts. We therefore turned to protein expression in the actinomycete Rhodococcus erythropolis, which we had previously found useful in generating soluble and active protein expressed from high-GCcontent genes (30,34,40). Using this system, soluble and active N-terminal His 6 -tagged Rgt1438 was successfully overexpressed and purified to homogeneity using a two-step chromatographic protocol (see Fig.…”
Section: Figmentioning
confidence: 99%
“…In this study, GW5074 demonstrated broad specificity against antibiotic kinases that play an important role in developing resistance in bacteria [52]. We wanted to test this theory and assess the ability of this compound to act synergistically with known antibiotics, like aminoglycosides, in killing S. aureus.…”
Section: Discussionmentioning
confidence: 99%